2014
DOI: 10.1002/anie.201400099
|View full text |Cite
|
Sign up to set email alerts
|

A Concerted Transfer Hydrogenolysis: 1,3,2‐Diazaphospholene‐Catalyzed Hydrogenation of NN Bond with Ammonia–Borane

Abstract: 1,3,2-diazaphospholenes catalyze metal-free transfer hydrogenation of a N=N double bond using ammonia-borane under mild reaction conditions, thus allowing access to various hydrazine derivatives. Kinetic and computational studies revealed that the rate-determining step involves simultaneous breakage of the B-H and N-H bonds of ammonia-borane. The reaction is therefore viewed as a concerted type of hydrogenolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
79
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(87 citation statements)
references
References 65 publications
6
79
0
2
Order By: Relevance
“…The N value of the six-membered N-hetercyclic P À H compound 1f [15] was also investigated in this work and included in Figure 4f or the same purpose.I tc an be seen from the right side of Figure 4that the PÀHcentered N scale covers over ten N units,r anking as 1a (25.5) @ 1b-e (20.9-17.7) @ 1f (13.5). [3] Thep owerfulness of 1a was also evidenced in other applications such as in catalytic reductions of imines, [5a] azocompounds, [7] pyridines, [9a] and CO 2 . Thes uper-hydricity of 1a was already confirmed by Gudat et al,w ho found that 1a can directly transfer ah ydride to aldehydes and diarylketones (within two minutes), and even to alkylketones (E = À22.30), although rather slowly.…”
Section: Zuschriftenmentioning
confidence: 99%
See 1 more Smart Citation
“…The N value of the six-membered N-hetercyclic P À H compound 1f [15] was also investigated in this work and included in Figure 4f or the same purpose.I tc an be seen from the right side of Figure 4that the PÀHcentered N scale covers over ten N units,r anking as 1a (25.5) @ 1b-e (20.9-17.7) @ 1f (13.5). [3] Thep owerfulness of 1a was also evidenced in other applications such as in catalytic reductions of imines, [5a] azocompounds, [7] pyridines, [9a] and CO 2 . Thes uper-hydricity of 1a was already confirmed by Gudat et al,w ho found that 1a can directly transfer ah ydride to aldehydes and diarylketones (within two minutes), and even to alkylketones (E = À22.30), although rather slowly.…”
Section: Zuschriftenmentioning
confidence: 99%
“…Gudat and co-workers seminal work demonstrated that 1a is af orm of super-hydride, [3] yet with common features of organic reagents, [4] such as relatively low cost and good solubility in organic media. Consequently,an umber of N-heterocyclic phosphorus hydrides ( Figure 1) and their analogues have been developed in recent years,rendering many originally infeasible reactions to occur under metal-free conditions,s uch as reductions of polar olefins, [5] imines, [5a] ketones, [6] and azo compounds, [7] valorization of CO 2 , [8] and hydroboration of pyridines. Consequently,an umber of N-heterocyclic phosphorus hydrides ( Figure 1) and their analogues have been developed in recent years,rendering many originally infeasible reactions to occur under metal-free conditions,s uch as reductions of polar olefins, [5] imines, [5a] ketones, [6] and azo compounds, [7] valorization of CO 2 , [8] and hydroboration of pyridines.…”
Section: Contrastingwiththewell-knownproticreactivityofconven-mentioning
confidence: 99%
“…Kinjo and co‐workers found that N‐heterocyclic phosphane 62 can quantitatively add to the N=N bond of an azobenzene to form N‐heterocyclic phosphinohydrazine 63 (R=Ph, Scheme ) . Subsequently, the P−N bond can be cleaved by addition of NH 3 ⋅BH 3 , giving diphenylhydrazine and regenerating the N‐heterocyclic phosphane 62 .…”
Section: Acid and Base‐catalyzed Dehydrogenationmentioning
confidence: 99%
“…[12] With the P III system, Kinjo and co-workers have shown that 2a can be employed in catalytic carbonyl hydroboration reactions,using HB(pin) to regenerate the P À Hb ond from the P À Ob ond formed during carbonyl reduction. [13] Both diazaphospholenes and tertiary phosphines have also been used in the hydroboration of carbon dioxide. [14] Scheme 1.…”
mentioning
confidence: 99%